2016
DOI: 10.1039/c6nr03008d
|View full text |Cite
|
Sign up to set email alerts
|

Glyco-gold nanoparticle shapes enhance carbohydrate–protein interactions in mammalian cells

Abstract: Advances in shape-dependent nanoparticle (NP) research have prompted a close scrutiny of the behaviour of nanostructures in vitro and in vivo. Data pertaining to cellular uptake and site specific sequestration of different shapes of NPs will undoubtedly assist researchers to design better nano-probes for therapeutic and imaging purposes. Herein, we investigated the shape dependent uptake of glyco-gold nanoparticles (G-AuNPs) in different cancer cell lines. Specifically, we have compared the behaviour of spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…Although it is well stated in the literature that in addition to a multivalent presentation, the ligand architecture [50], carbohydrate valency, density as well as carbohydrate type [51,52,53,54] and the spatial arrangement of carbohydrate ligands [55] can have an influence on carbohydrate lectin interactions, few studies have been performed on the effect of these factors on glyco-AuNP lectin binding. Kikkeri and coworkers found that the nanoparticle shape influences cellular uptake in different cancer cell lines [56] and studied the effect of heterogeneity of glycodendrons on bacterial binding [57]. Moreover, most studies showed an effect of the carbohydrate density and the spacer type and length in regard to undesirable aggregation in buffer medium [42,58,59] but only few studies investigated the effect of these factors on lectin binding [38,45].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well stated in the literature that in addition to a multivalent presentation, the ligand architecture [50], carbohydrate valency, density as well as carbohydrate type [51,52,53,54] and the spatial arrangement of carbohydrate ligands [55] can have an influence on carbohydrate lectin interactions, few studies have been performed on the effect of these factors on glyco-AuNP lectin binding. Kikkeri and coworkers found that the nanoparticle shape influences cellular uptake in different cancer cell lines [56] and studied the effect of heterogeneity of glycodendrons on bacterial binding [57]. Moreover, most studies showed an effect of the carbohydrate density and the spacer type and length in regard to undesirable aggregation in buffer medium [42,58,59] but only few studies investigated the effect of these factors on lectin binding [38,45].…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with variability in the relative number of mannose molecules involved in the NPs-bacteria interactions. The same group obtained similar results (higher responses of rod-modified NPs than in star and spherical particles) in in vitro experiments with mammalian cells [ 84 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 69%
“…Label-free detection of carbohydrate-protein binding using optical scattering or surface plasmon resonance on GNPs Reynolds et al, 2012;Tsutsumi et al, 2012;Richards et al, 2016;Sangabathuni et al, 2016 Using carbohydrate-GNPs as a fluorescence quencher to investigate lectin binding Budhadev et al, 2020 Monitoring microscopic localization of GNPs in the cell through electron micrograph…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…These particles are a very efficient light scatterer that changes their localized surface plasmon resonance frequency depending on the environment such as protein recognition of carbohydrate-coated GNPs (Tsutsumi et al, 2012 ; Richards et al, 2016 ). Therefore, GNPs have been utilized for label-free imaging and quantification of carbohydrate-protein interactions (Sangabathuni et al, 2016 ). In addition, GNPs have a strong fluorescent quenching property.…”
Section: Solid Nanoparticle Probes For Protein-carbohydrate Interactionsmentioning
confidence: 99%